The Influence of Employee Loyalty and Work Environment on Employee Work Productivity at CV. Umega Bahtera Sanjaya - Rayhan Demas Hafiyyan; Azis Azis; Rd. Herman Sofyandi (Quantitative Economics and Management Studies, 2023)
Business in Indonesia is currently experiencing rapid growth with the increasing number of new companies, making business competition in Indonesia increasingly high for business practitioners. One of the competitions is in the procurement of goods and services, which requires human resources that are able to compete and survive in the competition within a company's industrial activities. Carrying out business activities cannot be separated from the human resource management to complete the work and achieve the company's/organization's goals. This research is titled "The Influence of Employee Loyalty and Work Environment on Employee Work Productivity at CV. Umega Bahtera Sanjaya". The purpose of this study is to determine the influence of employee loyalty and work environment on employee work productivity at CV. Umega Bahtera Sanjaya. The research method used is descriptive and verification method. The research population is the employees of CV. Umega Bahtera Sanjaya. The sampling technique using the formula N=n resulted in a sample of 30 people, and the analysis method used is multiple regression and hypothesis testing. The results of this study indicate that employee work productivity is influenced by employee loyalty and work environment simultaneously. Employee loyalty is more dominant in employee work productivity, with the highest factor being the willingness to work together, which has a significant influence on employee work productivity. On the other hand, the work environment has a deficiency in security, which affects employee performance and comfort, leading to decreased productivity.